Implementasi Corporation Social Responsibility PT Unilever Indonesia Tbk Melalui Agenda Unilever Sustainable Living Plan (USLP) - Elok Rizki Windhia (Universitas 17 Agustus 1945 Jakarta, 2020)
MNCs or foreign companies in a country must have programs that are expected to be able to get their companies involved in the improvement and progress in society, one of which is Unilever companies in Indonesia. So the purpose of this research is to find out about the forms of social responsibility undertaken by Unilever through its USLP program in Indonesia. In this study we use the concept of CSR in researching about Unilever programs. Unilever has an empowerment program called USLP or Unilever Sustainable Living Plan, in several other countries having different kinds of USLP implementation. Unilever's USLP program in Indonesia by forming the Unilever Indonesia Foundation which has various activities carried out together with the community, especially in environmental empowerment, improving health quality, as well as providing empowerment to the entire community.Keyword : Unilever, CSR, Programs, USLP